2012
DOI: 10.1002/jbmr.1809
|View full text |Cite
|
Sign up to set email alerts
|

Femoral fracture rates after discharge from the hospital to the community

Abstract: Previous studies found that the risk of a femoral fracture in residents newly admitted to nursing homes was highest during the first months after admission and declined thereafter. Many nursing home admissions are preceded by a hospitalization. Therefore, the present study aimed to analyze if a similar risk pattern of fall-related fractures could also be observed in community-dwelling people at home after discharge from the hospital. Routine data of more than 690,000 German people aged 65 years and older with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This is in line with the study performed by Rapp et al who reported that this may have minor benefit for patients during the first weeks after discharge from hospital. This is in line with the study performed by Rapp et al who reported that exercise alone may have minor benefits for patients during the first weeks after discharge from hospital, and emphasise the importance of good discharge planning in order to optimize the support given to patients in their home environment to prevent future falls [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with the study performed by Rapp et al who reported that this may have minor benefit for patients during the first weeks after discharge from hospital. This is in line with the study performed by Rapp et al who reported that exercise alone may have minor benefits for patients during the first weeks after discharge from hospital, and emphasise the importance of good discharge planning in order to optimize the support given to patients in their home environment to prevent future falls [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…Potential causes of the observed pattern may be the new environment which is a challenge to many of the new and often cognitively impaired residents. Another German study found that patients hospitalized due to any reason had an increased risk for hip fractures during the first weeks after discharge from hospital to their homes [27]. A morbidity-related weakness with a deterioration of gait and balance, and a persisting (sub-acute) delirium may be further reasons for a transient increased risk of falls and fractures.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These aspects may have been responsible for an increased risk of falling. Another study in old community-dwelling people found that the first weeks after discharge from hospital were associated with an increased risk for femoral fractures [ 3 ]. A morbidity-related weakness with a deterioration of gait and balance, and a still (sub-acute) delirium may be further reasons for a transient increased risk of falling which could explain the observed time-dependent pattern.…”
Section: Introductionmentioning
confidence: 99%